Hi, I'm having trouble finding the inverse for this function:
Code:f(x) = sqrt(x)/(2x-3)
I know I need to swap f(x) for y and then solve for x, but I'm stuck on how to do that. Can anyone help me out?
What did you get after swapping?
I got
x = (2x-3)2y2
Then, expanding that polynomial I got
x = y2(2x2-12x+9)
But now I'm not sure where to go from here.
You have a quadratic equation in x.I got
x = (2x-3)2y2
Then, expanding that polynomial I got
x = y2(2x2-12x+9)
But now I'm not sure where to go from here.
You have a quadratic equation in x.
Rewrite what you have as 2(y^2)x^2 -[12(y^2)+1]x + 9y^2 =0.
Now use the quadratic formula with a=2y^2, b =-[12(y^2)+1] and c= 9y^2 to solve for x which is really y inverse. Show us your work up to here.
You opened 3 brackets but only closed 2! Just fix that.Thanks. So now I have (after simplifying):
x=(12y2+1 ± sqrt(24y2(3y2+1)+1)/4y2
I think that's simplified enough, so now I just have to switch x and y then I'll have the inverse, right?
You opened 3 brackets but only closed 2! Just fix that.
I am not sure why you factored out the 24y^2.
Did you try to factor 72y^4 + 24y^2 + 1??
Now we know that x>0 (why?), so you did to check to make sure that your solutions for x is never 0 or negative. Let us know your results to these questions.
Same sort of idea as already presented but another wayHi, I'm having trouble finding the inverse for this function:
Code:f(x) = sqrt(x)/(2x-3)
I know I need to swap f(x) for y and then solve for x, but I'm stuck on how to do that. Can anyone help me out?